Analgesic application of a novel non-steroidal anti-inflammatory drug imrecoxib after total knee arthroplasty: a prospective randomized controlled study - Guoyang Bai; Xiangxiang Sun; Qunli Dou; Bowei Li; Kai Qin; Xiaobo Sun; Jianbing Ma; Chao Xu; Yuanchi Huang (Perioperative Medicine)
Abstract Background Imrecoxib is a novel non-steroidal anti-inflammatory drug. As a moderately selective COX-2 inhibitor, it has achieved certain therapeutic effects in postoperative analgesia such as spinal, arthroscopic, and total hip arthroplasty. However, the efficacy of imrecoxib in postoperative analgesia after total knee arthroplasty (TKA) is still unknown. Therefore, this study aims to explore the clinical efficacy and safety of imrecoxib in postoperative analgesia after TKA. Methods The 120 patients were randomly assigned to two groups. The experimental group was given one tablet of imrecoxib 4 h after surgery in addition to conventional treatment. Starting from the second day, the dose of imrecoxib was 0.1 g/time, twice a day. The control group only received conventional treatment. The observation indicators included visual analogue scale (VAS) score, joint range of motion (ROM), opioid consumption, erythrocyte sedimentation rate (ESR), C-reactive protein (PCR), interleukin-6 (IL-6), and incidence of adverse reactions. Results At rest, the VAS pain scores of the experimental group at 24 and 48 h after surgery (3.033 ± 1.154, 2.700 ± 0.988) were lower than those of the control group (2.017 ± 0.128, 1.950 ± 0.589), with statistical differences (P = 0.000 < 0.05, P = 0.000 < 0.05). At movement state, the VAS scores of the experimental group at four postoperative time points (4.050 ± 0.805, 4.633 ± 1.048, 4.517 ± 1.057, 4.233 ± 0.844) were lower than those of the control group (4.433 ± 0.782, 5.067 ± 0.910, 5.800 ± 0.945, 5.167 ± 1.003), with statistical differences (P = 0.013 < 0.05, P = 0.027 < 0.05, P = 0.000, P = 0.000).The joint ROM of the experimental group at 24 h (84.783 ± 7.902) and 48 h (86.403 ± 10.367) was higher than that of the control group (76.725 ± 9.499, 79.802 ± 8.400), with statistical differences (P = 0.000 < 0.05, P = 0.000 < 0.05).The postoperative opioid consumption of the experimental group (0.567 ± 0.692) was significantly lower than that of the control group (2.783 ± 1.156), with a statistical difference (P = 0.000 < 0.05). Conclusion Our prospective randomized controlled trial demonstrates that imrecoxib can effectively alleviate postoperative pain after TKA, reduce opioid dosage, and does not cause additional adverse reactions, providing a new option for analgesic treatment after TKA. Trial registration The study was registered with the China Clinical Trial Registry (registration number: ChiCTR2300072839). Registered date: 20,230,616.